Kenya's Vision 2030: Modelling Technology Usage and the Economy - Omamo, Amos O; Rodrigues, Anthony J; Muliaro, Wafula (Pergamon, 2019)
Kenya has emerged in recent times as one of the fastest growing telecom markets in the world. Assessing the impact of existing and emerging mobile technologies on individuals and societies is a complex task. Various models of the information society have been developed and they differ from country to country. There is not a single, widely used paradigm which has synthesised the various schools and theories dealing with technology and society. These fragmented approaches do not have a fully-fledged mode of application to the relationship of ICT and (information) society. The models developed so far do not provide satisfying directions for policy purposes. This paper argues that the issue of mobile technology on society is a complex technical and social phenomenon that needs to be understood from both ICT and social science perspectives. This study used the concept of governance socio-techno-economic systems as the theoretical framework. We use system dynamics as both the methodology and tool to model the mobile industry impact on society. It is hoped that by understanding the process, a developing country may have clear directions on how to design its technology policies. The study resulted in an important finding that the social capital intensity is affected by corruption in a negative direction. The study shows that the increase in social capital intensity is an important source of the economic growth. This increase will strengthen the accelerator mechanism of the economy and creates larger multiplier effects. The increase in social capital intensity can be obtained through managing innovation processes base on the development of education and the R&D capacity of the nation.